النظام القانوني للعون المتربص في ظل 06-03الأمرالتطبیقیة ونصوصه - رزوق سفيان- بن زيد اليزيد (جامعة المسيلة, 2024)
The study dealt with the legal system of the lurking aid under Order 06-03, and the applied text represented in Executive Decree No. 17-322. The topic derives its importance from the importance of the public service and the employee in society, as well as the role of the lurking stage in revealing the extent of the employees' eligibility for demarcation. Therefore, the problem of the topic revolved around the extent to which the legislator reconciled the balance between protecting the lurking from the abuse of the administration, as well as the need to reveal the period of lurking on its validity for demarcation, and to answer it. Descriptive and analytical approaches were used, starting with studying the theoretical and conceptual framework for lurking in the public service, and then analyzing its legal system, through the process of probation (its duration, the assessment of the lurking, the effects of lurking), the system of rights and duties, and detailing in its disciplinary system, especially the system of sanctions independent of the employee. The study reached the specificity of the legal system of the lurking and distinguishing it from the legal status of the employee in terms of some rights and the expansion of the discretionary authority of the administration in extending the legal
Keywords: Lurking Aid; Legal System; Order 06-03; Executive Decree 17-322.